PENGARUH MINAT BELAJAR DAN KEMANDIRIAN BELAJAR TERHADAP HASIL BELAJAR SISWA KELAS X MIPA MATERI TRIGONOMETRI - Windy Natalia Tandiayu; Sugeng Sugeng; Berahman Berahman (IKIP Siliwangi, 2023)
This study aims to determine the effect of interest in learning and learning independence on student learning outcomes on trigonometry material for class X MIPA SMA Negeri in Bontang City. The type of research is quantitative research with ex-post facto method. The population of this research is the students of class X MIPA SMA Negeri in Bontang City which consists of 12 classes of 427 students, with the Cluster Random Sampling technique obtained 6 classes of 204 students. The research instrument uses learning outcomes tests and questionnaires. The data analysis technique used descriptive statistical analysis and inferential statistical analysis (multiple regression) with = 0.05. Based on the results of descriptive statistical analysis, interest in learning and learning independence is included in the medium category, while learning outcomes are included in the less category. From the results of the simultaneous test, obtained a value (Sig. F = 0.004) which means the regression model means. From the results of the partial test, interest in learning has a significant effect on student learning outcomes (Sig. t = 0.034) and for independent learning learning independence has no significant effect on student learning outcomes (Sig. t = 0.715).